The Impacts of Simulated Microgravity on The Cell Viability and Claudin-1 and Claudin-3 Expression of MCF-7 Breast Cancer Cells - Margrita Adamian; Azadeh Hekmat; Zahra Hajebrahimi (Journal of Sciences, Islamic Republic of Iran)
It has been believed that microgravity directly can alter the structure, morphology, and function of biosystems and numerous research have been performed to recognize these alterations. Claudin proteins are the tight junctions’ main components. Additionally, they are crucial for the protection of the differentiated state of epithelial cells as well as for cell-cell interaction. This study aimed to explore the probable correlation between the claudin-1 and claudin-3 expression and microgravity condition. Additionally, examined the impacts of microgravity condition on cell morphology and viability. The gene expression in MCF-7 cells were assessed by real-time quantitative RT PCR. Afterward, the morphology and cellular viability of the cells were evaluated by an inverted microscope, MTT assay, and flow cytometry analysis. After 72 h of simulated microgravity, the claudin-1 and claudin-3 expression increased significantly (P<0.05). Also, MCF-7 cells after 72 h exposure to microgravity simulation comprised rounded cells, which were grouped and linked to each other making multicellular spheroids. However, microgravity simulation after 24 or 72 h did not have a remarkable effect on the viability of cells. The consequence of this research lied in the fact that simulated microgravity could not be a direct cure for breast cancer treatment. However, microgravity research can offer a unique in vitro tool to explore biomechanical effects in the biology of cancer. The findings obtained from this investigation can open fascinating research lines in astrobiology, biophysics, and cancer biology and can be utilized to improve survivability and life quality for malignancy patients.